2013
DOI: 10.1038/nri3406
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin signalling in immune homeostasis and the control of microorganisms

Abstract: Lymphotoxin (LT) is a member of the tumour necrosis factor (TNF) superfamily that was originally thought to be functionally redundant to TNF, but these proteins were later found to have independent roles in driving lymphoid organogenesis. More recently, LT mediated signalling has been shown to actively contribute to effector immune responses. LT regulates dendritic cell and CD4+ T cell homeostasis in the steady state and determines the functions of these cells during pathogenic challenges. The LT receptor path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 110 publications
(204 reference statements)
4
93
0
Order By: Relevance
“…NF-B is a positive regulator of FasL expression thus supporting our finding that NKG2D-induced activation of NF-B increased FasL expression and enhanced tumor cell killing (Kasibhatla et al, 1999). Lymphotoxins ␣ and ␤ are members of the TNF superfamily and have been found to mediate inflammation and target cell lysis, and to play a role in the defense against viruses and tumors (Upadhyay and Fu, 2013;Ware, 2005). Interestingly, coexpression of FasL and LT␣ on effector CD8 + T cells can induce strong anti-tumor responses, thus the NKG2D-induced increase of these proteins will likely contribute to enhanced immunity (Dobrzanski et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…NF-B is a positive regulator of FasL expression thus supporting our finding that NKG2D-induced activation of NF-B increased FasL expression and enhanced tumor cell killing (Kasibhatla et al, 1999). Lymphotoxins ␣ and ␤ are members of the TNF superfamily and have been found to mediate inflammation and target cell lysis, and to play a role in the defense against viruses and tumors (Upadhyay and Fu, 2013;Ware, 2005). Interestingly, coexpression of FasL and LT␣ on effector CD8 + T cells can induce strong anti-tumor responses, thus the NKG2D-induced increase of these proteins will likely contribute to enhanced immunity (Dobrzanski et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…Other proteins that are induced by the NF-B pathway are members of the TNF superfamily, TNF␣ and lymphotoxins (LT) ␣ and ␤, all of which have important roles in inducing inflammatory immune responses (Upadhyay and Fu, 2013;Ware, 2005). In CD8 + T cells, CD3/NKG2D stimulation increased gene expression of TNF␣ and LT␣ and ␤ compared to stimulation through CD3/CD28 or CD3 alone (Fig.…”
Section: Activation Through the Tcr And Nkg2d Increases Proinflammatomentioning
confidence: 97%
“…At this locus, the lymphotoxin-alpha ( LTA ) and TNFA genes are closely juxtaposed with the LTA coding region part of the TNFA early promoter region. While previous findings suggested that LTA shared a common signaling pathway with TNFA to mediate inflammatory responses [92], recent evidence suggests that the LTA and TNFA signaling pathways are unique [93, 94]. In the literature [95], rs1041981 is described as a SNP in both the LTA (i.e., coding region) and TNFA (i.e., promoter region) genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LT-or LTβ receptor-deficient mice have impaired splenic structure and lack peripheral lymphoid tissues such as lymph nodes and Peyer's patches (Randall et al, 2008;Vondenhoff et al, 2007). Since LT signaling and LT-mediated lymphoid tissue-specific chemokine expressions play an important role in secondary lymphoid tissue development and maintenance (Cyster, 1999;Fu et al, 1997;Upadhyay and Fu, 2013), the decreased LTα expression and chemokines in the absence of PrP C may partially and/or indirectly involved in impaired splenic structure.…”
Section: Number Of Lti Cells and The Expression Of Lt And Cxcr5 In Lmentioning
confidence: 97%